FECAL BACTERIA CRUDE EXTRACTS FROM PHILIPPINE NATIVE CHICKEN (GALLUS GALLUS DOMESTICUS) SHOW ANTIMICROBIAL ACTIVITY AGAINST STAPHYLOCOCCUS AUREUS - FBR Matias; JH Pastorano; MBS Salinas (Exploratory Animal and Medical Research, 2020)
Generally, the study evaluated the in vitro antimicrobial activity of fecal bacteria isolated from Philippine native chicken against Staphylococcus aureus. Specifically, this study measured the antimicrobial activity of the crude extracts from fecal bacteria cultured at different time intervals and compared them with selected antimicrobials against S. aureus. A loopful of isolated fecal bacteria was cultured in nutrient broth at different time intervals (6, 12, 18, and 24 h). After each time interval, the broth culture was centrifuged at 6,000 rpm for 15 min and the cell-free supernatant (crude extract) was collected. Sterile filter paper discs were impregnated with a total of 30 µl crude extracts and placed on spread plate culture of S. aureus on Mueller-Hinton (MH) agar, including selected antimicrobials discs (2 µg clindamycin, 5 µg enrofloxacin, and 10 µg penicillin V), then incubated at 37 °C for 18 to 24 h. The zones of inhibition were measured using a Vernier caliper and compared. The crude extracts of fecal bacteria from different breeds of Philippine native chicken have antimicrobial activity against S. aureus as shown by various sizes of the zone of inhibition. The Banaba breed had the greatest number of isolates with the zone of inhibition. The crude extracts that produced a zone of inhibition were significantly higher compared to selected antimicrobials - clindamycin and penicillin V, but significantly lower compared to enrofloxacin.